Global status and trends in heart failure with preserved ejection fraction over the period 2009-2020: A bibliometric analysis. Issue 11 (18th March 2022) - Dong, Qiuju; Zhang, Junwei; Han, Qinghua; Zhang, Hongzhen; Wang, Meiling; Huang, Qi; Zhao, Jianping
Abstract: Background: Heart failure with preserved ejection fraction (HFpEF) comprises about 50% of the cases of heart failure (HF), but so far there is no effective treatment strategy. This study used bibliometric methods to analyze the scientific literature on HFpEF in 2009 to 2020, and evaluate the global scientific output of HFpEF research, in order to explore the research status and trends in this field. Methods: Documents about the HFpEF research published in 2009 to 2020 were retrieved from Science Citation Index Expanded (SCIE) in Web of Science. This study used bibliometrix R-package, VOSviewer, and CiteSpace to conduct the bibliometric analysis. Results: A total of 1971 documents (1508 articles and 283 reviews) were retrieved to construct the local HFpEF literature collection for analysis. The number of annual documents had increased year by year in general, from 24 to 353. Relevant documents were mainly written in English, and mostly focused on the field of "Cardiovascular System Cardiology." USA ranked first in the relevant countries/regions with most documents, and the leading affiliation was Mayo Clin. Shah SJ was the most productive author, while Borlaug BA ranked highest among the local cited authors and G-index. Circulation was the most local cited source, while Eur J Heart Fail published the most documents and was rated as the top source in terms of G-index. "Paulus WJ, 2013, J Am Coll Cardiol" was the top local cited document within the local HFpEF literature collection, while "Owan TE, 2006, New Engl J Med" outside the local HFpEF literature collection was the most local cited reference. The keywords such as "mortality, " "dysfunction, " "diagnosis, " "outcomes, " and "diastolic dysfunction" were most frequent, while "hemodynamics, " "comorbidity, " "myocardial infarction, " "inflammation, " and "phenotype" indicated research frontiers or emerging trends. Furthermore, this study also found some deeper bibliometric relationships through bibliographic networks. Conclusions: Due to the multi-dimensional bibliometric analysis, this study shows a wide view of scientific productivity related to HFpEF, and provides valuable guidance for researchers interested in HFpEF, assisting them in understanding the research status, identifying potential collaborators, discovering research hotspots and frontiers, and conducting more in-depth research.